2019
DOI: 10.1111/aogs.13549
|View full text |Cite
|
Sign up to set email alerts
|

Maternal short‐term complications after planned cesarean delivery without medical indication: A registry‐based study

Abstract: | INTRODUC TI ONTechnology constantly challenges our perception of best practice regarding healthcare. During the mid-1990s and early 2000s the rates of cesarean section in Denmark rose rapidly, from 12.8% in 1996 to 20.8% in 2006, 1 only to stabilize around 20% since then. 1 As a result of this development, several hospitals are currently trying to reduce the rate of cesarean deliveries in Denmark, 2,3 this with reference to higher rates of maternal complications associated with cesarean delivery when compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Several studies have compared CSMR to vaginal delivery and analyzed groups’ characteristics, obstetric outcomes, short-term complications in puerperium and showed no increase in major complications in CS [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have compared CSMR to vaginal delivery and analyzed groups’ characteristics, obstetric outcomes, short-term complications in puerperium and showed no increase in major complications in CS [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a recent Danish study from 2019 showed no increase in major complications associated with CSMR but an increased rate of wound infections [ 39 ]. This research identifies the women who ask for CS and confirms the exclusion of major complications in women that request caesarean delivery, as previously mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Still, CS is in general associated with increased risk for short-term and long-term health complications for both mother and child, and are increasing with repeated caesareans. 9 While the risk for short-term complications (including wound infections) are relatively low following planned caesarean delivery, [10][11][12] complications can occur in subsequent pregnancies such as abnormal placentation, uterine rupture, unexplained fetal death and postpartum haemorrhage. [13][14][15] Consequently, decision-making, especially for first-time pregnancies, should involve consideration of future pregnancies and implications across the reproductive lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…However, the large increase in CS use, often for non-medical indications, accounts for negative consequences in maternal and child health (4). Wound complications are surprisingly a high problem after CS and contribute to increased risks in subsequent pregnancies (5,6). The risk of associated morbidities is progressively increasing as the number of previous cesarean deliveries increases (7,8).…”
mentioning
confidence: 99%